A Critical Analysis of Van Dijk’s Model: The Construction of Meaning and Representations of State Losses in Online News Coverage of the Case Involving the Former CEO of PT ASDP - Ayuni Ika Aulia (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study investigates the construction of meaning in online news discourse concerning corruption through the application of Teun A. Van Dijk’s Critical Discourse Analysis model, focusing on a news article reporting state financial losses in the case of a former director of PT ASDP. Employing a qualitative empirical approach, the research utilizes textual data as the primary source and applies qualitative content analysis to examine the structural, cognitive, and social dimensions embedded within the discourse. The findings reveal that the macrostructure emphasizes financial loss as the central theme, while the superstructure organizes information to reinforce institutional legitimacy through a systematic narrative of legal authority. At the micro level, linguistic features such as lexical choices, syntax, and rhetorical strategies contribute to selective representation, highlighting certain actors while marginalizing others, thereby shaping public perception. Furthermore, the analysis of social cognition indicates that journalistic perspectives are influenced by dominant anti-corruption ideologies, which guide the framing and interpretation of events. In the broader social context, the discourse functions to reproduce power relations and institutional dominance, reflecting the interplay between media practices and socio-political structures in contemporary Indonesia.